2006
DOI: 10.4049/jimmunol.177.4.2088
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Ligands Induce Higher IFN-α Production in Females

Abstract: IFN-α exercises multiple immune modulatory and antiviral activities and has been suggested to play a critical role in the pathogenesis of systemic lupus erythematosus (SLE). Plasmacytoid dendritic cells (pDCs) release IFN-α upon TLR7 and TLR9 ligation. With respect to the nine times higher incidence of SLE in women and the clinical use of synthetic TLR ligands as novel immune adjuvants, we analyzed IFN-α and TNF-α production in healthy human individuals. Blood samples were incubated with synthetic TLR7 and TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
339
8
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(389 citation statements)
references
References 67 publications
34
339
8
8
Order By: Relevance
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our data adds to previous reports on the influence of sex on production of IFNα by pDCs, demonstrating that also surface maturation markers are upregulated more in female pDCs (Berghöfer et al, 2006;Meier et al, 2009;Seillet et al, 2012Seillet et al, , 2013. The effect of sex on upregulation of especially CD40 but also CD86 was respectively mostly or partially explained by the rs179008 variant allele.…”
Section: Discussionsupporting
confidence: 69%
“…Incomplete X-inactivation of TLR7 may contribute to the effects of sex. Although previous studies found no evidence for incomplete or skewed X-inactivation this was recently challenged by Souyris and colleagues who reported that pDC express more TLR7 in females due to escape of X-inactivation (Schott et al, 2007a;Berghöfer et al, 2006;Souyris et al, 2018). Besides, TLR7 function may be enhanced by female hormones and/or enhanced expression of molecules downstream of TLR7 (Seillet et al, 2012(Seillet et al, , 2013Griesbeck et al, 2015).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It has been reported that TLR7 ligands induced higher IFN␣ production in females (31) and that 17␤-estradiol promoted TLR4-triggered proinflammatory mediator production (32). In the present study, we demonstrated that 17␤-estradiol enhanced CD40 expression and DC maturation with or without CpG, which is the ligand of TLR9.…”
Section: Discussionsupporting
confidence: 63%
“…Sex differences in immune responses have been described. For instance, higher production of interferon-a by activated peripheral blood mononuclear cells from women compared with cells from men has been described (Bergho¨fer et al, 2006). Interestingly, interferon-a restores normal b 1 -integrin-mediated inhibition of leukemic progenitor proliferation (Bhatia et al, 1996) and RACK1 has been shown to be a partner of both integrin and interferon-a receptor (Kubota et al, 2002;Kiely et al, 2008).…”
Section: Discussionmentioning
confidence: 99%